1995
DOI: 10.1093/jnci/87.11.817
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer in Radon-Exposed Miners and Estimation of Risk From Indoor Exposure

Abstract: In the miners, about 40% of all lung cancer deaths may be due to radon progeny exposure, 70% of lung cancer deaths in never-smokers, and 39% of lung cancer deaths in smokers. In the United States, 10% of all lung cancer deaths might be due to indoor radon exposure, 11% of lung cancer deaths in smokers, and 30% of lung cancer deaths in never-smokers. This risk model estimates that reducing radon in all homes exceeding the U. S. Environmental Protection Agency's recommended action level may reduce lung cancer de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
189
1
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(200 citation statements)
references
References 0 publications
7
189
1
3
Order By: Relevance
“…The risk increased with estimated cumulative exposure and decreased with attained age, time since exposure, and time since cessation of exposure (National Research Council, 1999). The excess RR estimated from occupational cohorts, which included over 2500 cases of lung cancer occurring among over 60 000 miners, has been estimated in the order of 0.0049 per working level month of exposure (Lubin et al, 1995). Further refinements of this estimates took into account age at exposure and time since first exposure (National Research Council, 1999), as well as smoking status, with a stronger effect being shown among never-smokers than among smokers.…”
Section: Ionizing Radiationmentioning
confidence: 99%
“…The risk increased with estimated cumulative exposure and decreased with attained age, time since exposure, and time since cessation of exposure (National Research Council, 1999). The excess RR estimated from occupational cohorts, which included over 2500 cases of lung cancer occurring among over 60 000 miners, has been estimated in the order of 0.0049 per working level month of exposure (Lubin et al, 1995). Further refinements of this estimates took into account age at exposure and time since first exposure (National Research Council, 1999), as well as smoking status, with a stronger effect being shown among never-smokers than among smokers.…”
Section: Ionizing Radiationmentioning
confidence: 99%
“…The decay products of radon emit alpha particles of high energy and mass that may damage nuclear DNA of cells in the lungs and airways. In fact, a very high risk of LC (40%) was observed in underground miners of uranium who had been exposed to radon chronically (70). In the study, the rates of deaths from LC were 70% and 39% for never-smokers and current smokers, respectively (70).…”
Section: Radiationmentioning
confidence: 69%
“…Another explanation might be found in the interaction between radon exposure and smoking, a habit much more prevalent among males than among females in Japan. In fact, animal experiments reveal a multiplicative synergistic relationship 11) and studies with miners suggest a superadditive relationship 1) between smoking and radon exposure. Unfortunately, no smoking data for individual study subjects were available for this study.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a pooled analysis on data from 11 studies of radon-exposed miners showed that over the full range of radon exposure, to as low as 50-100 WLM, the relative risk relationship remains linear. 1) Hei et al reported that many cells may survive traversal by one to four particles to express a dose-dependent increase in the frequency of mutations, 17) which may provide a biological basis for the validity of utilizing data from miners, although mutation may not be directly related to the carcinogenic process. However, the fact that air in underground mines may contain other lung carcinogens or irritants, and the differences in mode of exposure acquisition contribute uncertainties to the linear extrapolation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation